Alternative exon skipping biases substrate preference of the deubiquitylase USP15 for mysterin/RNF213, the moyamoya disease susceptibility factor - Kotani, Yuri (Sci Rep, 2017)
The deubiquitylating enzyme USP15 plays significant roles in multiple cellular pathways including TGF-β signaling, RNA splicing, and innate immunity. Evolutionarily conserved skipping of exon 7 occurs during transcription of the mRNAs encoding USP15 and its paralogue USP4, yielding two major isoforms for each gene. Exon 7 of USP15 encodes a serine-rich stretch of 29 amino acid residues located in the inter-region linker that connects the N-terminal putative regulatory region and the C-terminal enzymatic region. Previous findings suggested that the variation in the linker region leads to functional differences between the isoforms of the two deubiquitylating enzymes, but to date no direct evidence regarding such functional divergence has been published. We found that the long isoform of USP15 predominantly recognizes and deubiquitylates mysterin, a large ubiquitin ligase associated with the onset of moyamoya disease. This observation represents the first experimental evidence that the conserved exon skipping alters the substrate specificity of this class of deubiquitylating enzymes. In addition, we found that the interactomes of the short and long isoforms of USP15 only partially overlapped. Thus, USP15, a key gene in multiple cellular processes, generates two functionally different isoforms via evolutionarily conserved exon skipping.